Media and Social History: Duta Masyarakat Newspaper Response Towards PKI (Partai Komunis Indonesia) in The Post-Gestapu (Gerakan September Tiga Puluh) Tragedy of 1965 - Afghani, RP. M Himam Awan; Muzaiyana, Muzaiyana; Khairani, M. Sirajuddin Bin A (JURNAL INDO-ISLAMIKA, 2024)
This research is entitled ‘Media and Social History: Duta Masyarakat Response Towards PKI (Partai Komunis Indonesia) in the Post Gestapu (Gerakan September Tiga Puluh) Tragedy Of 1965’. This research aims to examine how Duta Masyarakat newspaper, as one of the Islamic mass media, responded to the PKI after Gestapu event and how this response shaped public opinion at that time. The approaches used in this research are sociological approach and critical discourse analysis, using agenda setting and framing theories.The results showed that Duta Masyarakat played a crucial role in shaping public opinion towards PKI by emphasising the perspectives of Islam and Nationalism. The media used framing that favoured anti-communist and pro-national stability narratives. by setting a selective news agenda and providing certain framing, Duta Masyarakat succeeded in shaping public opinions and providing legitimacy to repressive action taken by the military and some people’s militia after the Gestapu event